Analisis Muhassinat Lafziyyah Melalui Iqtibās Dalam QS. Al-Baqarah Ayat 269: Studi Tentang Pemberian Ilmu dan Hikmah - Fadwa Nabilah (Asosiasi Riset Ilmu Pendidikan Agama dan Filsafat Indonesia, 2025)
This study examines the beauty of the language of the Qur'an through the balaghah device, especially in the aspect of muhassinat lafziyyah with a focus on the iqtibas technique in QS. Al-Baqarah verse 269. Muhassinat lafziyyah is a form of embellishment of words that beautify the sound, rhythm, and structure of language, while strengthening the message conveyed. One of the important elements in it is iqtibas, which is the citation of the words of the Qur'an or Hadith in another sentence structure without explicitly mentioning the source. This study uses a qualitative approach with a library research method that refers to primary sources such as books on balaghah science, as well as secondary sources in the form of scientific articles and journals. Based on the results of the analysis, QS. Al-Baqarah verse 269 is categorized as a form of Iqtibas Kulli, where the quotation is done in full without changing the words. This verse emphasizes that wisdom is a special gift from Allah that includes depth of knowledge, accuracy of thinking, and the wise practice of knowledge in life. Thus, this study confirms that the beauty of the wording of the Qur'an is not only aesthetically valuable, but also strengthens the content of deep meaning, showing the synergy between the beauty of language and the depth of content in conveying divine messages.